Designing a Balanced Scorecard Using a Scenario Approach [Diseño de Cuadro de Mando Integral Con Enfoque de Escenario] - Palominos-Belmar, P; Quezada-Llanca, L (Emerald Group Holdings Ltd., 2019)
Purpose: The purpose of this paper is to design a method or process that relates dynamic environmental conditions with the strategic objectives present in a company’s strategy map, thereby allowing rapid analysis and the generation of new strategies that the company can adopt in a timely manner in order to maintain and/or improve its competitive position in the market. Design/methodology/approach: One training session and three workshops were run involving the company staff. The intervention team reviewed and analyzed the results achieved and prepared the final presentation. Finally, they were asked to evaluate the intervention methodology with respect to usefulness and ease of use. Findings: The developed methodology allows companies to obtain a broader vision of their future prospects. The executives’ participation in the process provided them a vision and understanding of the most relevant and sensitive variables of their environment. Research limitations/implications: The proposed methodology is easy to use. It provides a simple and agile mechanism to adapt the strategy of an organization to the changes in the market and environment. Social implications: This process will provide social benefit for the global community, from both a methodological perspective and a practical one, as it will provide a tool that will positively impact competitiveness and quality of life for workers and the wider community. Originality/value: This paper allows the identification of the possible scenarios and their incorporation into a strategy map, which may help companies deal with the changes in their competitive environment. The strategy maps generated for each of the scenarios provide useful information with respect to presented events. © 2019, Emerald Publishing Limited.